Selective binding of benzoquinone with a Pt-II-cyclophane constructed on the skeleton of N,N `-bis(salicylidene)-p-phenylenediamine: synthesis and spectroscopic studies - Kumari, Niraj; Prajapati, Rishikesh; Dixit, Mudit; Mishra, Lallan (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2009)
The Schiff base NN'-bis(salicylidene)-p-phenylenediamine has been complexed with Pt(en)Cl-2 and the resulting Pt-II-cyclophane, [Pt(en)L](2)center dot 4PF(6), reacted with phenol, resorcinol, hydroquinone or benzoquinone in DMSO solution. Their binding has been monitored by the variation in the corresponding UV-visible and emission spectral patterns. The binding properties are compared with the earlier reported Zn-II-cyclophane [Zn(bpy)L](2) (bpy = 2,2'-bipyridine). A few solid adducts of phenol and benzoquinone with the Pt-II-cyclophane complex and hydroquinone as well as that of resorcinol with the Zn-cyclophane have also been synthesized and characterized.
Keywords: Coordination chemistry; Cyclophanes; Metallocyclophanes; platinum; Schiff bases

Ab initio and periodic DFT investigation of hydrogen storage on light metal-decorated MOF-5 - Dixit, Mudit; Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2011)
The effect of light metal (M = Li, Be, Mg, and Al) decoration on the stability of metal organic framework MOF-5 and its hydrogen adsorption is investigated by ab initio and periodic density functional theory (DFT) calculations by employing models of the form BDC:M-2:nH(2) and MOF-5:M-2:nH(2), where BDC stands for the benzenedicarboxylate organic linker and MOF-5 represents the primitive unit cell. The suitability of the periodic DFT method employing the GGA-PBE functional is tested against MP2/6-311 + G* and MP2/cc-pVTZ molecular calculations. A correlation between the charge transfer and interaction energies is revealed. The metal-MOF-5 interactions are analyzed using the frontier molecular orbital approach. Difference charge density plots show that H-2 molecules get polarized due to the charge generated on the metal atom adsorbed over the BDC linker, resulting in electrostatic guest-host interactions. Our solid state results show that amongst the four metal atoms, Mg and Be decoration does not stabilize the MOF-5 to any significant extent. Li and Al decoration strengthened the H-2-MOE-5 interactions relative to the pure MOF-5 exhibited by the enhanced binding energies. The hydrogen binding energies for the Li- and Al-decorated MOF-5 were found to be sensible for allowing reversible hydrogen storage at ambient temperatures. A high hydrogen uptake of 4.3 wt.% and 3.9 wt.% is also predicted for the Li- and Al-decorated MOF-5, respectively. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ab initio calculations; Density functional theory; Hydrogen binding energies; Hydrogen storage; Metal-Pi-Arene interactions

Scandium-decorated MOF-5 as potential candidates for room-temperature hydrogen storage: a solution for the clustering problem in MOFs - Dixit, Mudit; Maark, Tuhina Adit; Ghatak, Kamalika; Ahuja, Rajiv; Pal, Sourav (Journal of Physical Chemistry C, 2012)
Transition-metal-based systems show promising binding energy for hydrogen storage but suffer from clustering problem. The effect of light transition metal (M = Sc, Ti) decoration, boron substitution on the hydrogen storage properties of MOF-5, and clustering problem of metals has been investigated using ab initio density, functional theory. Our results of solid-tate calculations reveal that whereas Ti clusters strongly Sc atoms do not suffer from this problem when decorating MOF-5. Boron substitution on metal-decorated MOF-5 enhances the interaction energy of both the metals with MOF-5. Sc-decorated MOF-5 shows a hydrogen storage capacity of 5.81 wt % with calculated binding energies of 20-40 kJ/mol, which ensures the room-teniperature applicability of this hydrogen storage material.

Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films: first-principle DFT computations supporting the systematic experimental endeavor - Sharma, Vidhika; Dixit, Mudit; Satsangi, Vibha R.; Dass, Sahab; Pal, Sourav; Shrivastav, Rohit (International Journal of Hydrogen Energy, 2014)
Photoelectrochemical splitting of water with nanocrystalline Zn1-xMnxO thin films was investigated. ZnO thin films with 1, 3, 5 and 7% at. Mn incorporation were synthesized by sol gel method and characterized by X-Ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), X-ray Photoelectron spectroscopy (XPS), High Resolution Transmission Electron Microscopy (HR-TEM) and UV-Vis spectroscopy. Mn incorporation coupled with variation in sintering temperature led to significant microstructural changes, which tentatively influenced the magnitude of optical absorption and charge carrier mobility, thereby impacting the performance of such systems towards photoelectrochemical splitting of water. Electronic structure computations based on first principle density functional theory (DFT) revealed electronic states of Mn being responsible for the marginally recorded red shift in bandgap energy. Photoelectrochemical measurements using thin films of 1% at. Mn:ZnO sintered at 600 degrees C yielded 3 times enhanced photocurrent at zero bias due to improved optical absorption. Plausible explanations for the effect have also been offered. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Hydrogen energy; Mn doped ZnO; Optical properties; Photoelectrochemical water splitting

Hydrogen adsorption in ZIF-7: A DFT and ab-initio molecular dynamics study - Dixit, Mudit; Major, Dan Thomas; Pal, Sourav (Chemical Physics Letters, 2016)
Primary H-2 adsorption sites in a zeolitic imidazolate framework, ZIF-7, are identified using ab-initio density functional theory (DFT) based molecular dynamics annealing simulations. The simulations suggest several low energy adsorption sites. The effect of light transition metal decoration on hydrogen storage properties was studied. Our ab-intio DFT calculations illustrate that decorating the ZIF with Sc increases both the number of H-2 molecules, as well as the H-2 binding energy. The binding energy (similar to 25 kJ/mol per H-2) at 8H(2) loading in the pore, suggests that Sc-ZIFs can be potential candidates for hydrogen storage. (C) 2016 Elsevier B.V. All rights reserved.

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.